Damages and Benefits of Certification: A perspective from an Independent Assessment Body - Fusani, Mario; Marchetti, Eda (Electronic Communications of the EASST, 2010)
The paper investigates on the nature of software certification and its reasons of being. The numerous factors that impact on the achievement of its purposes are discussed, and also compared in the cases of Proprietary Software and Open Source Software. Some relevant features of a certification process for Open Source Software are finally proposed.